Blood pressure-lowering and cardiovascular effects of plumbagin in rats: An insight into the underlying mechanisms - Maira Ahmad; Taseer Ahmad; Hafiz Muhammad Irfan; Nabeela Noor (Elsevier, 2022)
Background: Plumbagin, a natural phenolic compound is investigated for response against blood pressure and vascular reactivity. Methodology: Blood pressure lowering effects were observed by in-vivo invasive evaluation in normotensive rats, and in-vitro experimentation to measure changes of tension in isolated rat aorta and contractility in atria. Results: The percentage decrease in mean arterial pressure (MAP) observed with plumbagin intravenously at doses of 0.1, 0.5, 1, 5, 10 ​μg/kg in normotensive rats was 7.16 ​± ​2.35, 15.5 ​± ​5.62, 19.5 ​± ​5.27, 26 ​± ​6.67, 34.33 ​± ​8.80, respectively. Plumbagin exerted vasorelaxant effects in rat aorta, unaffected by the removal of vascular endothelium, and L-NAME and methylene blue pretreatment. Plumbagin completely inhibited phenylephrine (1 ​μM) and High K+ (80 ​mM) induced contractions. Similar to a Ca+2 channel antagonist, plumbagin caused a rightward shift in the Ca+2 concentration-response-curves (CRCs), resembling nifedipine. Pre-incubation with plumbagin, significantly suppressed contractions induced by phenylephrine in Ca+2-free medium via disrupting Ca+2 release from intracellular stores. No change in vasorelaxant response was observed with the addition of potassium channel blockers, TEA and BaCl2. In rat atrial strips, plumbagin exerted significant negative inotropic and chronotropic effects. No significant change was observed with atropine and atenolol pretreatment, so the effect appeared independent of muscarinic and beta-adrenergic receptors. Conclusion: This study suggests the blood pressure lowering effects of plumbagin. That could be contributed by a decrease in vascular resistance via calcium antagonism, interferences in calcium efflux, and depressive effects on the rate and force of cardiac contraction. Further studies would be necessary to probe deeper into the underlying mechanisms.